2015
DOI: 10.12740/pt/31993
|View full text |Cite
|
Sign up to set email alerts
|

Body image and self-esteem of patients with onco-hematological diseases after chemotherapy

Abstract: Aim. To measure interactions between body image and self-esteem in patients with onco-hematological diseases. Method. The study included 30 patients with diagnosis of acute leukemia or lymphoma at the beginning of chemotherapy and control group of 30 healthy people. The study uses a structured interview, Body Image Scale, Rosenberg Self-Esteem Scale, Tennessee Self Concept Scale, Profile of Mood States. Results. The higher level of concerns, care and poorer body image in patients body was found in comparison t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…In her studies involving 30 patients of hematology departments following chemotherapy, Tomasiewicz revealed that their body image was worse than in the group of healthy women, with similar values assigned to appearance in both groups. The patients largely followed the recommendations regarding personal hygiene in order to improve their appearance and accelerate the treatment process . It appears that the eagerness to maintain or return to the looks from the time before the disease may contribute to medication adherence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In her studies involving 30 patients of hematology departments following chemotherapy, Tomasiewicz revealed that their body image was worse than in the group of healthy women, with similar values assigned to appearance in both groups. The patients largely followed the recommendations regarding personal hygiene in order to improve their appearance and accelerate the treatment process . It appears that the eagerness to maintain or return to the looks from the time before the disease may contribute to medication adherence.…”
Section: Discussionmentioning
confidence: 99%
“…The patients largely followed the recommendations regarding personal hygiene in order to improve their appearance and accelerate the treatment process. 26 It appears that the eagerness to maintain or return to the looks from the time before the disease may contribute to medication adherence. This finding should be important for the personnel taking care of oncological patients, and who have to deal with the side effects of the disease and its treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Co warte jest podkreślenia, myśli Z. Balickiego, dotyczące wychowania (egoizm narodowy), nie znajdują odzwierciedlenia w koncepcjach NOP. Podobnie Roman Dmowski, uważany za autorytet ruchu narodowego, nie znajduje w oczach NOP zbytniego poparcia ze względu na to, iż nie "uważa go się za twórcę skończonej ideologii polskiego nacjonalizmu" 63 . Ipso facto kierunek rozwoju jednostki prezentowany w Myślach nowoczesnego Polaka mimo, iż nie uważany jest za teoretyczną podbudowę mogącą stanowić o formie, w jakiej owo wychowanie mogło by przebiegać, staje się podstawą, na jakiej wychowanie narodowe miałoby się opierać.…”
Section: Idea Nacjonalistycznego Wychowaniaunclassified
“…People with high self-esteem have good adaptability ( 13 ). However, changes in body image among patients with hematologic malignancies due to the side effects of radiotherapy and chemotherapy can cause low self-esteem ( 14 ). Low self-esteem is likely to lead to depression, which can have a negative impact on patients' physical and mental health ( 13 , 15 ).…”
Section: Introductionmentioning
confidence: 99%